Analysis of gut microbiota changes in alcoholic fatty liver disease in progression based on 16S rDNA sequencing technology - DONG Xiaowei; WU Changliang; WANG Zhenchang; QIN Suping; HE Jianke; HUANG Huiyi (Guangxi Yike Daxue xuebao)
Objective To analyze the changes of gut microbiota in the progression of alcoholic fatty liver disease(AFLD) using 16S rDNA sequencing technology, and to explore the possible mechanism of AFLD progression in mice. Methods A total of 60 male C57BL/6 mice were randomly divided into control group (n=35) and model group (n=25). After adaptive feeding for 5 days, mice in the control group were fed a control Lieber-DeCarli fluid feeds (TP4030C) daily, and mice in the model group were fed Lieber-DeCarli fluid feeds (TP4030B) containing 4% ethanol daily. After 30 consecutive days, hematoxylin-eosin (HE) staining was used to observe the pathological changes of the liver. 16S rDNA sequencing was used to analyze the composition and structure of gut microbiota. Results Compared with the control group, Alpha diversity results of the gut microbiota of mice in the AFLD model group showed reduced species richness (P < 0.05). Beta diversity results indicated significant differences in the structural composition and abundance of the gut microbiota of the two groups of mice (P < 0.05). Compared with the control group, the relative abundance of Faecalibaculum, Dubosiella, Allobaculum, Ruminococcaceae UCG-013 were higher in the model group, while the relative abundance of Lactobacillus and Lachnospiraceae NK4A136 group were lower in the model group. The activity of gut microbiota in alanyltransferase, glutathione hydrolase and histone acetyltransferase pathways was significantly increased in the model group of mice (P < 0.05). Conclusion AFLD C57BL/6 mouse model is successfully constructed on Lieber-DeCarli fluid feeds containing 4% ethanol, and both the structure and composition of the gut microbiota of AFLD mice are altered. Alcohol may accelerate the progression of AFLD by disrupting gut microbial homeostasis and increasing the activities of alanyltransferase, glutathione hydrolase, and histone acetyltransferase pathways.